Epidemiological profile of patients utilising public oral health services in Limpopo province, South Africa - Lawrence K. Thema; Shenuka Singh (AOSIS, 2017)
Background: Despite the impact of oral diseases on the quality of life, there is limited updated evidence on oral health status in Limpopo province. Objectives: To determine the epidemiological profile of patients utilising public oral health services in Limpopo province. Method: This was a descriptive retrospective clinical chart review conducted in five purposively selected district hospitals in Limpopo province. The collected data included the patient's sociodemographic information, reasons for dental consultation, information on the dental or oral diseases and the treatment received. Five hundred clinical files were systematically selected (100 from each district hospital) for the period 01 January 1995 to 31 December 2013. Data were collected using the World Health Organization's indicator age groups, namely 6-year-olds, 12-year-olds, 18-year-olds and 35-44-year-old groups. A data capturing sheet was used to record the collected information. Data were analysed using the statistical software package for social sciences SPSS version 23.0. Results: The majority of patients were in the age group of 6 to 20 years (n = 375, 75%). The majority were male patients (n = 309; 62%). Dental caries was the most common complaint (n = 298, 60%). The second most common main complaint in this age group was retained primary or deciduous teeth (n = 60, 12%) affecting children mainly in the age group of 6 to 12 years. The most common clinical procedure across all five districts was dental extractions (n = 324, 64%). Other clinical interventions included scaling and polishing (n = 33, 12%) and dental restorative care (n = 20, 3%). Conclusion: There is an urgent need to reorient oral health service delivery in Limpopo province to focus more on preventive oral health programmes.